Purification of crude glycerine from biodiesel waste using activated carbon - Lau, Kia Kian (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Crude glycerine is a by-product from the biodiesel industry. The growing of biodiesel industry recently has caused surplus of crude glycerine. High purity of glycerine component is valuable and it can be obtained by purifying the crude glycerine. A combination of physicochemical methods can be integrated with batch adsorption to purify the bio-based crude glycerine into high purity of glycerine as the final product which can be commercialized to pharmaceutical, cosmetic, chemical, food and beverage industries. In this research work, adsorption by different concentrations of activated carbons in purifying palm oil-based crude glycerine was studied and conducted with a series of pretreatment stages which include acidification, neutralization, solvent extraction and evaporation. The utilization of chemicals and reagents which were able to contribute to the highest glycerine content in pretreatment or physicochemical stages was performed by considering the justification and statements of previous research works. From the results obtained after experimental works, application of activated carbons with 200 g/L gave the maximum 96.7 wt% glycerine content with the clearest colour of glycerine product following implementation of a series of pretreatment stages. This purity fulfilled the glycerine specification of MS 1507:2001.